The Role of Community Participation in the Optimizing Education Services Quality: A Case Study of SMP IT Darul Fikri North Bengkulu - Ewin Sumarti; Manap Somantri; Muhammad Kristiawan (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This study explores the role of community participation in optimizing the quality of education services at SMP IT Darul Fikri, a junior high school in North Bengkulu, Indonesia. Employing a qualitative case study design, data were collected through in-depth interviews with school principals, teachers, committee members, and parents, supplemented by observations and document analysis. The findings indicate that community participation, primarily facilitated through Parent-Teacher Association (POMG) meetings, plays a critical role in planning, implementing, and monitoring school. Programs particularly religious programs like Qur’an memorization (tahfidz). This active involvement, especially in home-based monitoring, significantly contributes to program effectiveness and service quality. The study concludes that structured community forums like POMG are vital for fostering collaboration between schools and communities, leading to improved educational outcomes. This research highlights a sustainable model for educational quality enhancement in contexts with limited government support, emphasizing the need for participatory management.